THE APPLICATION OF GUIDED INQUIRY APPROACH BASED ON VIRTUAL LABORATORY TO INCREASE STUDENTS LEARNING OUTCOME OF GLOBAL WARMING IN SMA MUHAMMADIYAH 2 SURABAYA - PRANSISKA INDRA L., FIFA (Inovasi Pendidikan Fisika, 2017)
The research objective was to describe the increasing of students’ learning outcome in global warming topic by implementing guided inquiry based on the virtual laboratory. The learning outcome which increased were cognitive and skill competence. The research used pre-experimental with one group pretest-posttest design and used three class as sample namely XI MIPA 1, XI MIPA 2, and XI MIPA 3 of SMA Muhammadiyah 2 Surabaya. The increasing of students learning outcome was analyzed by paired sample t test and normalized gain. The result of this research showed that (1) the learning process was conducted very good; (2) the students cognitive competence increased significantly in high rate and the students skill competence increased significantly in medium rate; (3) the students responses due to physics learning based on virtual laboeatory of global warming was very good. Based on those result it showed that implementation of guided inquiry approach based on virtual laboratory could increase the students learning outcome. Keywords: virtual laboratory, kognitive competence, skill competence, global warming.